Collaborative Pediatric Healthcare Approaches Addressing Adolescent Anxiety, Depression, And Emotional Development Through Community Partnerships Today - Langade, Dr Mrs R A; Arora, Rohini; R, Savitha; Shrimal, Gajendra; Sirish, B.; K, Ravindran; Sahu, Dr. Prabhat Kumar; Sasikumar, Dr. P. (Adolescência e Saúde, 2026)
The problem of adolescent anxiety and depression is an increasing issue of health concern in a population that negatively influences emotional growth, school performance, social performance, and psychological stability in the long term. Cooperative pediatric healthcare models that bring together healthcare professionals, schools, families, and community organizations have been suggested as effective methods of dealing with these issues. This was a research to analyze the usefulness of collaborative pediatric healthcare strategy in managing adolescent anxiety and depression and emotional development using community partnerships. The analytical study was carried out between January and April 2026 on 200 teenagers aged 13-18 years specific to schools and community health centers in urban and semi-urban areas using stratified random sampling. The means of collecting data were standardized anxiety and depression assessment scales, emotional development questionnaire and community partnership participation survey. The statistical analysis was conducted with SPSS version 27.0, where the descriptive statistics, Pearson correlation analysis and multiple regression with a significance level of p less than 0.05 were used. The results showed moderate level of anxiety (38.5) and severe anxiety (21.0), moderate level of depression (32.0) and severe depression (16.5). Teenagers that took part in collaborative pediatric healthcare programs scored significantly higher on emotional development scores (4.12 ± 0.58) compared to teenagers with limited engagement (3.41 ± 0.71; p < 0.001). Community partnership engagement had found negative relations with anxiety (r = -0.52, p < 0.001) and depression (r = -0.47, p < 0.001), and strong positive relations with emotional development (r = 0.63, p < 0.001). The regression analysis has found family support (0.38, p < 0.001), participation in healthcare activities at schools (β = 0.29, p = 0.002) and community participation (0.34, p < 0.001) to be significant factors predicting emotional development. The research comes up with the conclusion, that collaborative models of pediatric health care with strong community-based partnerships have a positive impact on anxiety and depression symptom reduction, alongside emotional development in adolescents. Making integrated healthcare, family, school, and community partnerships more robust can offer sustainable benefits of mental health and the overall well-being of adolescents.